PERAN FINANCIAL TECHNOLOGY PADA PEMBIAYAAN PEER TO PEER SYARIAH TERHADAP PERTUMBUHAN USAHA KECIL: PENDEKATAN ANALYTIC NETWORK PROCESS - Nida Hafia; Ahmad Mulyadi Kosim; Abrista Devi (Kasaba, 2020)
Financial technology (Fintech) is proof the development of digital technology that provides innovation in the form of a financial service provider, it certainly will affect economic growth in Indonesia. Fintech in Indonesia has not been fully utilized by the public especially Fintech Sharia Peer to Peer Lending. widespread activity based on digital creates challenges and opportunities to develop businesses / businesses for MSMEs, challenges faced by one of them MSME mindset that is not yet in tune with technological developments. MSME businesses can access Islamic financial services products and apply for financing directly without having to go to Islamic finance offices. With this like then can increase financial inclusion and encourage MSME business growth. Using a method Analytic Network Process (ANP) of this research try to decipher the factors which affects the growth of the MSME business MSMEs in the form of Benefit, Opportunity, Cost, Risk criteria and formulate Strategy as acceleration optimize the role of fintech sharia peer to peer lending in encouraging the growth of the MSME business. The results of the analysis of data processing shows the cluster opportunity criteria be the main factor which can given fintech sharia peer to peer lending to encourage the growth of the MSME and the followed by the Benefit, Cost and Risk criteria. Financial education and socialization to MSMEs became the highest agreement of the experts as an effort to optimize the role fintech sharia peer to peer lending in encouraging the growth of the MSME.